A lingüística indígena no Brasil - Seki, Lucy (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This article presents a panorama of the area of the linguistics of the indigenous languages in Brazil within the discipline of Brazilian linguiistics as a whole. Special attention is given to those aspects related to its specific development. It is argued that in contrast to what is commonly supposed, the arrival of the Summer Institute of Linguistics (1959) not only was not the beginning of this area of study in the country, but it even contributed to the delay in its establishment. It was only after the return of Brazilian scholars educated abroad who were interested in the study of the national indigenous languages that a specialized branch of linguistics directed to the study of these languages began to take form. The present situation of the area and perspectives for future development are both explored.